Social information technology [ connecting society and cultural issues - Chen, Irene; Kidd, Terry T. (Information Science Reference, 2008)
"This book provides a source for definitions, antecedents, and consequences of social informatics and the cultural aspect of technology. It addresses cultural/societal issues in social informatics technology and society, the Digital Divide, government and technology law, information security and privacy, cyber ethics, technology ethics, and the future of social informatics and technology"--Provided by publisher.